Arch Preserver Shoes display booth - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows Bloom's shoe store display for Arch Preserver Shoes. A variety of signs appear throughout the display. One of the signs reads, "Keep good feet good" and another reads, "Arch Preserver Shoes sold exclusively in San Jose at Bloom's." Material from a large tent appears above this scene.